MRI evaluation of the ACL remnant tissue in ACL-deficient knee - Tsuneari Takahashi; Masashi Kimura; Katsushi Takeshita (Journal of Orthopaedic Surgery, 2017)
Purpose: To clarify the relationship between anterior cruciate ligament (ACL) remnant tissue at the time of surgery and preoperative evaluation of ACL-injured knee. Methods: A total of 123 patients were enrolled and classified into four groups based on the classification of ACL remnant tissue. To quantify the signal–noise quotient (SNQ), five regions of interest (ROIs), such as tibial, mid, femoral ACL remnant, tendon of quadriceps femoris to normalize the signal intensity of ACL remnant tissue, and background measurements, were measured. Preoperative side-to-side difference (SSD) and SNQ were analyzed. Results: Significant differences were observed in preoperative SSD of the four groups ( p = 0.021), and a post hoc analysis revealed that SSD in Crain type 2 was significantly smaller than that in Crain type 4 ( p = 0.014). SSD in Crain type 3 was also significantly smaller than that in Crain type 4 ( p = 0.0030). There were significant differences in SNQ at the tibial, mid, and femoral portion in Crain types 2 and 3 ( p < 0.001); SNQ at the tibial portion in Crain type 2 was significantly lower than that at the mid portion ( p = 0.024); and SNQ at the tibial portion in Crain type 3 was significantly lower than that at the mid portion ( p = 0.016). Furthermore, significant differences were observed in SNQ at the tibial portions in the four groups ( p = 0.034), and SNQ at the tibial portions in Crain type 2 was significantly lower than that in Crain type 1 ( p = 0.044). Also, SNQ at the tibial portions in Crain type 3 was significantly lower than that in Crain type 1 ( P = 0.035). Conclusion: The femoral attachment of the ACL remnant tissue may influence the SNQ of the tibial remnant tissue and the stability of the ACL-injured knee.